Are the Domains Considered by ICF Comprehensive Enough to Conceptualize Participation in the Patient with Hand Injuries? - Farzad, Maryam; Layeghi, Fereydoun; Hosseini, Seyyed Ali; Hamidreza, Khanke; Asgari, Ali (Journal of Hand and Microsurgery, 2017)
Background Although participation is a core concept in multiple models of disability, there is no consensus on its definition.Objective The aim of this study was to extract participation domains based on review of theories, available outcome measures, and interviews with experts and the person with hand injuries to compare with the ICF domains of participation.Methods A qualitative approach using a deductive content analysis was employed to extend definitions of participation from theories. Later on, inductive qualitative method using semistructured interview with five experts in different fields and 30 patients with different hand injuries was used. Coding was performed with extracted domains from the content of data, and finally, the extracted domains were compared with the ICF domains of participation.Results Some of the extracted domains were not considered in ICF.Conclusion Subjective participation is the main forbearance part. Role, leisure, domestic life, environment, and others are also main missing meanings. This limitation can hinder measuring disability and health.
Keywords: participation; ICF; disability; hand injuries